THE ANALYSIS OF ACCOUNTING TREATMENTS BASED ON GOVERNMENT ACCOUNTING STANDARDS (GAS) ON INTANGIBLE ASSETS (IA) IN NATIONAL NUCLEAR DEVELOPMENT AGENCY - Budi Kaliwanto; Sri Agustini (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2018)
Government Regulation Number 71 of 2010 dated October 22, 2010 onGovernment Accounting Standard (GAS) states that the Government applies Accrual Based GAS and is declared in Statement of Government Accounting Standards (SGAS). While the technical accounting explanation used as a guide is published in the form of GAS Technical Bulletin. In the case of Intangible Assets (IA), the Government Accounting Standards Committee (GASC) issued Bulletin No. 17 on Accounting for Intangible Assets based on Accruals. The implementation of the Technical Bulletin was used as the basis for the preparation of the IA Report in the National Nuclear Energy Agency (BATAN). Management and Preparation of BATAN's Financial and State Property (BFSP) reports using management flows, consistency of established amortization methods, impairment, discontinuation and disposal of IA. In the preparation of the IA Report, BATAN as a government institution is increasingly required to adapt to changes in government management systems that demand accountabilityprinciples, in which every state administration must be accountable for theperformance or outcomes of all programs and activities to the community for the use of resources and authority given. The result of testing of research instrument showed that IA data processing in BATAN based on the grouping of 5 categories (Copyright, Patent, Software, Result of Research / Research, and other Intangible Assets) outlined the value of the Copyright asset has the smallest value and the other IA has the greatest value (can be seen on the results of the discussion on pages 9-15).